An early indicator for anomalous stock market performance - Fritz, Marlon; Gries, Thomas; Wiechers, Lukas (Quantitative Finance)
We propose an indicator for detecting anomalous stock market valuation in real time such that market participants receive timely signals so as to be able to take stabilizing action. Unlike existing approaches, our anomaly indicator introduces three methodological novelties. First, we use an endogenous, purely data-driven, nonparametric trend identification method to separate long-term market movements from more short-term ones. Second, we apply SETAR models that allow for asymmetric expansions and contractions around the long-term trend and find systematic stock price cycles. Third, we implement these findings in our indicator and conduct real-time market forecasts, which have so far been neglected in the literature. Applications of our indicator using monthly S&P 500 stock data from 1970 to the end of 2022 show that short-term anomalous market movements can be identified in real time up to one year ahead. We predict all major anomalies, including the 1987 Bubble and the initial phase of the Financial Crisis that began in 2007. In total, our anomaly indicator identifies more than 80% of all – even minor – anomalous episodes. Thus, smoothing market exaggerations through early signaling seems possible.
Keywords: General Economics; Econometrics and Finance; Finance

Realization of high-fidelity unitary operations on up to 64 frequency bins - De, Syamsundar; Ansari, Vahid; Sperling, Jan; Barkhofen, Sonja; Brecht, Benjamin; Silberhorn, Christine (Physical Review Research)
The ability to apply user-chosen large-scale unitary operations with high fidelity to a quantum state is key to realizing future photonic quantum technologies. Here, we realize the implementation of programmable unitary operations on up to 64 frequency-bin modes. To benchmark the performance of our system, we probe different quantum walk unitary operations, in particular, Grover walks on four-dimensional hypercubes with similarities exceeding 95% and quantum walks with 400 steps on circles and finite lines with similarities of 98%. Our results open a path toward implementing high-quality unitary operations, which can form the basis for applications in complex tasks, such as Gaussian boson sampling. Published by the American Physical Society 2024

Dimensioning and Lifetime Prediction Model for a Hybrid, Hydrogen-Based Household PV Energy System Using Matlab/Simulink - Möller, Marius Claus; Krauter, Stefan (Solar)
This paper presents a model of an energy system for a private household extended by a lifetime prognosis. The energy system was designed for fully covering the year-round energy demand of a private household on the basis of electricity generated by a photovoltaic (PV) system, using a hybrid energy storage system consisting of a hydrogen unit and a lithium-ion battery. Hydrogen is produced with a Proton Exchange Membrane (PEM) electrolyser by PV surplus during the summer months and then stored in a hydrogen tank. Mainly during winter, in terms of lack of PV energy, the hydrogen is converted back into electricity and heat by a fuel cell. The model was created in Matlab/Simulink and is based on real input data. Heat demand was also taken into account and is covered by a heat pump. The simulation period is a full year to account for the seasonality of energy production and demand. Due to high initial costs, the longevity of such an energy system is of vital interest. Therefore, this model was extended by a lifetime prediction in order to optimize the dimensioning with the aim of lifetime extension of a hydrogen-based energy system. Lifetime influencing factors were identified on the basis of a literature review and were integrated in the model. An extensive parameter study was performed to evaluate different dimensionings regarding the energy balance and the lifetime of the three components, electrolyser, fuel cell and lithium-ion battery. The results demonstrate the benefits of a holistic modelling approach and enable a design optimization regarding the use of resources, lifetime and self-sufficiency of the system

Learning Computational Thinking in Secondary School (Year 8) in Germany in International Comparison: Results from ICILS 2018 - Labusch, Amelie; Eickelmann, Birgit (Teaching coding in K-12 schools: Research and application)

Definition of High-Risk Motion Patterns for Female ACL Injury Based on Football-Specific Field Data: A Wearable Sensors Plus Data Mining Approach - Di Paolo, Stefano; Nijmeijer, Eline M.; Bragonzoni, Laura; Gokeler, Alli; Benjaminse, Anne (Sensors)
The aim of the present study was to investigate if the presence of anterior cruciate ligament (ACL) injury risk factors depicted in the laboratory would reflect at-risk patterns in football-specific field data. Twenty-four female footballers (14.9 ± 0.9 year) performed unanticipated cutting maneuvers in a laboratory setting and on the football pitch during football-specific exercises (F-EX) and games (F-GAME). Knee joint moments were collected in the laboratory and grouped using hierarchical agglomerative clustering. The clusters were used to investigate the kinematics collected on field through wearable sensors. Three clusters emerged: Cluster 1 presented the lowest knee moments; Cluster 2 presented high knee extension but low knee abduction and rotation moments; Cluster 3 presented the highest knee abduction, extension, and external rotation moments. In F-EX, greater knee abduction angles were found in Cluster 2 and 3 compared to Cluster 1 (p = 0.007). Cluster 2 showed the lowest knee and hip flexion angles (p < 0.013). Cluster 3 showed the greatest hip external rotation angles (p = 0.006). In F-GAME, Cluster 3 presented the greatest knee external rotation and lowest knee flexion angles (p = 0.003). Clinically relevant differences towards ACL injury identified in the laboratory reflected at-risk patterns only in part when cutting on the field: in the field, low-risk players exhibited similar kinematic patterns as the high-risk players. Therefore, in-lab injury risk screening may lack ecological validity.
Keywords: Electrical and Electronic Engineering; Biochemistry; Instrumentation; Atomic and Molecular Physics; and Optics; Analytical Chemistry

Choice architecture interventions promoting sustained healthier food choice and consumption by students in a secondary school setting: A systematic review of intervention studies - Schulte, Eva A.; Winkler, Gertrud; Brombach, Christine; Buyken, Anette (Public Health Nutrition)
Abstract Objective: To systematically review the impact of choice architecture interventions (CAI) on the food choice of healthy adolescents in a secondary school setting. Factors potentially contributing to the effectiveness of CAI types and numbers implemented and its long-term success were examined. Design: PUBMED and Web of Science were systematically searched in October 2021. Publications were included following predefined inclusion criteria and grouped according to number and duration of implemented interventions. Intervention impact was determined by systematic description of the reported quantitative changes in food choice and/or consumption. Intervention types were compared with regards to food selection and sustained effects either during or following the intervention. Setting: CAI on food choice of healthy adolescents in secondary schools. Participants: Not applicable Results: Fourteen studies were included; four randomized controlled trials and five each of controlled or uncontrolled pre-post design, respectively. Four studies implemented a single CAI type, with ten implementing > 1. Three studies investigated CAI effects over the course of a school year either by continuous or repeated data collection, while ten studies’ schools were visited on selected days during intervention. Twelve studies reported desired changes in overall food selection, yet effects were not always significant, and appeared less conclusive for longer term studies. Conclusions: This review found promising evidence that CAI can be effective in encouraging favorable food choices in healthy adolescents in a secondary school setting. However, further studies designed to evaluate complex interventions are needed.
Keywords: Public Health; Environmental and Occupational Health; Nutrition and Dietetics; Medicine (miscellaneous)

IndQNER: Named Entity Recognition Benchmark Dataset from the Indonesian Translation of the Quran - Gusmita, Ria Hari; Firmansyah, Asep Fajar; Moussallem, Diego; Ngonga Ngomo, Axel-Cyrille (Natural Language Processing and Information Systems)
Indonesian is classified as underrepresented in the Natural Language Processing (NLP) field, despite being the tenth most spoken language in the world with 198 million speakers. The paucity of datasets is recognized as the main reason for the slow advancements in NLP research for underrepresented languages. Significant attempts were made in 2020 to address this drawback for Indonesian. The Indonesian Natural Language Understanding (IndoNLU) benchmark was introduced alongside IndoBERT pre-trained language model. The second benchmark, Indonesian Language Evaluation Montage (IndoLEM), was presented in the same year. These benchmarks support several tasks, including Named Entity Recognition (NER). However, all NER datasets are in the public domain and do not contain domain-specific datasets. To alleviate this drawback, we introduce IndQNER, a manually annotated NER benchmark dataset in the religious domain that adheres to a meticulously designed annotation guideline. Since Indonesia has the world’s largest Muslim population, we build the dataset from the Indonesian translation of the Quran. The dataset includes 2475 named entities representing 18 different classes. To assess the annotation quality of IndQNER, we perform experiments with BiLSTM and CRF-based NER, as well as IndoBERT fine-tuning. The results reveal that the first model outperforms the second model achieving 0.98 F1 points. This outcome indicates that IndQNER may be an acceptable evaluation metric for Indonesian NER tasks in the aforementioned domain, widening the research’s domain range.

Life-cycle health effects of compulsory schooling - Schmitz, Hendrik; Tawiah, Beatrice Baaba
We study the effect of education on health (hospital stays, number of diagnosed conditions, self-rated poor health, and obesity) over the life-cycle in Germany, using compulsory schooling reforms as a source of exogenous variation. Our results suggest a positive correlation of health and education which increases over the life-cycle. We do not, however, find any positive local average treatment effects of an additional year of schooling on health or health care utilization for individuals up to age 79. An exception is obesity, where positive effects of schooling start to be visible around age 60 and become very large in age group 75-79. The results in age group 75-79 need to be interpreted with caution, however, due to small sample size and possible problems of attrition.
Keywords: Education; health; life-cycle effects; compulsory schooling

The effect of compulsory schooling on vaccination against COVID and Influenza - Monsees, Daniel; Schmitz, Hendrik
We study the effect of education on vaccination against COVID-19 and influenza in Germany and Europe. Our identification strategy makes use of changes in compulsory schooling laws and allows to estimate local average treatment effects for individuals between 59 and 91 years of age. We find no significant effect of an additional year of schooling on vaccination status in Germany. Pooling data from Europe, we conclude that schooling increases the likelihood to vaccinate against COVID by an economically negligible effect of one percentage point (zero for influenza). However, we find indications that additional schooling increases fear of side effects from COVID vaccination.
Keywords: COVID; influenza; vaccination; education; compulsory schooling

Learning the pronunciation of segmental features of english phonology at german primary schools - Hahn, Charlotte Anna
In der vorliegenden Arbeit wird die Auswirkung expliziter Ausspracheübungen auf die englische Aussprache von Kindern an Grundschulen in NRW untersucht. Das Ziel dieser Arbeit ist es, eine Alternative für den mittel-offenen vorderen Vokal /æ/ und die dentalen Frikative /, ð/ zu bieten. Es wurde eine Interventionsstudie mit 72 Teilnehmenden aus drei verschiedenen Grundschulklassen durchgeführt; zwei vierte Klassen mit verschiedenen Lehrkräften und eine dritte Klasse, die von der Lehrperson einer der vierten Klassen unterrichtet wurde. Jede Klasse wurde in eine Kontroll- und zwei Interventionsgruppen (je eine für den Vokal und die Konsonanten) geteilt. Alle Gruppen wurden einmal zu Beginn und zwei Mal am Ende der Studie getestet. Zwischen den letzten beiden Tests lagen sechs bis acht Wochen, um einen mittelfristigen Effekt zu testen. Die Intervention, die nach der ersten Messung stattfand, wurde auf zwei je ca. drei-minütige Einzelsitzungen aufgeteilt. Während der Intervention übten die Teilnehmenden mit der Autorin die Aussprache des relevanten Phonems. Die Ergebnisse dieser Studie zeigen, dass die Interventionen einen Effekt auf die Aussprache der Teilnehmenden hatten. Wie sich dieser Effekt verhält und entwickelt scheint von der Art des Phonems, dem Alter der Teilnehmenden sowie der bisherigen Ausspracheschulung abzuhängen. Die vorliegenden Ergebnisse liefern Erkenntnisse nicht nur für die Grundschule selbst, sondern auch für die Lehrer*innenausbildung und Lehrplanentwicklung.